PUBLICATION ACTIVITY OF UKRAINIAN HEI ACADEMIC STAFF: A CASE STUDY - Vinnikova, Nataliia; Kuzmenko, Olga; Karpenko, Anastasiya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the Ukrainian education and science systems globalization and European integration processes have raised the issue of visibility for Ukrainian scientists. Having the articles in Scopus and Web of Science indexed journals is becoming of particular significance for scientists' authority rise and universities` prestige. Despite the appropriate state of the educational policy, the publishing activity of the majority of Ukrainian Higher Education Institutions’ academic staff still remains insufficient, and to date, a very few empirical research has been carried out to determine reasons for that. The aim of this study was therefore, to investigate how such factors as corporate culture of Borys Grinchenko Kyiv University, academic career, research and language skills, personal development, financial support etc. contribute to and prevent successful publication activity of University`s academic staff. Two groups of academicians were interviewed. The results showed that it is necessary to create the conditions for the research culture development, develop the research competence, provide systemic monitoring of publication activity, and improve the mechanisms of financial rewards.